Entrepreneur characteristics and determinants of self-employment across Europe - Dermot Coates; Martina Lawless (The Economic and Social Research Institute (ESRI), 2024)
Entrepreneurship is a key driver of jobs and innovation. This paper examines the prevalence of entrepreneurship across Europe and characteristics of those who become entrepreneurs. We place a particular focus on the distinction between opportunity and necessity motivations for becoming self-employed. The results in this paper find that one of the most significant barriers to entrepreneurship in Europe is lack of access to finance although this is noticeably lower in Ireland. Examining the characteristics of the self-employed, we find that participation by women and those in younger age cohorts (19-24 and 25-29) are significantly lower than for other groups. The results also suggest that considerations related to personal finances are amongst the main difficulties encountered in being selfemployed.
Keywords: 330; Entrepreneurship; Selbstständige; Unternehmensgründung; Arbeitszufriedenheit; Europa